The Relationship of Health Literacy Levels Related to Smoking with Exacerbation Frequency and Sleep Quality in Individuals with Chronic Obstructive Pulmonary Disease - Olcar, Tuğba; Uysal, Hilal (Current Respiratory Medicine Reviews, 2025)
IntroductionThe descriptive study was conducted to determine the relationship between health literacy levels related to smoking, the frequency of exacerbations, and sleep quality in individuals with Chronic Obstructive Pulmonary Disease.MethodsThe study data were collected from 217 patients who were hospitalized in the pulmonology service of a university hospital between October 1, 2022, and January 31, 2023, who applied to the outpatient clinic between October 1, 2022, and January 31, 2023, by face-to-face interview method and by obtaining verbal and written informed consent. The data collection tools used in the study were the patient information form, chronic obstructive pulmonary disease assessment test, pittsburgh sleep quality scale, and smoking literacy scale.ResultsIt was determined that 24% of the individuals were 60 years old or younger, 42.9% were 61-70, and 33.2% were over 70. It was determined that 25.8% of the individuals were still smoking, 49.3% of the individuals had never been hospitalized due to an exacerbation in the last year, 32.3% had been hospitalized once, and 18.4% had been hospitalized twice or more. General views about smoking increased the level of sleep quality (β = -0.152). The total change in sleep quality level was explained by smoking literacy at a rate of 7.2% (R2 = 0.072). Smoking literacy increases the improvement of sleep quality levels (β = -0.275). Smoking literacy increases the improvement in COPD assessment level (β = -0.238). It was determined that the smoking literacy levels of the individuals were high, the severity of Chronic Obstructive Pulmonary Disease was at a poor level, and sleep quality was at a moderate level.ConclusionIn the study, it was determined that the severity of chronic obstructive pulmonary disease decreased as the smoking literacy level of individuals increased, sleep quality level increased as the smoking literacy level increased, and chronic obstructive pulmonary disease staging worsened as smoking literacy total scores decreased.
Keywords: chronic obstructive pulmonary disease